Hermeneutic Perspectives on Bioethics in Intercultural and Interethnic Contexts (Revista Iberoamericana de Bioética, 2026)
Based on the reports and voices of Mapuche users who attend the traditional and intercultural hospitals present in the Araucanía region, this work seeks to clarify whether these narratives are present in the bioethical discussions generated within the Healthcare Ethics Committees (CEA) when making clinical or therapeutic decisions. To do this, apart from the documentary review, the work involved the semi-structured interview, which considers a sample of members of different CEAs in Araucanía, as well as Mapuche users. The first findings show the importance of the story and narrative of the users at the time of the anamnesis, as well as the importance for the Mapuche patient of the active presence of the “other”, both in the process of diagnosis and treatment. These interviews confirm the presence of “non-theoretical knowledge”, understood as a “conceptual imaginary”, regarding what is understood by interculturality in the biomedical field. This enables the understanding of the foundations on which the discussion in a CEA is based. The problem is approached from a narrative hermeneutic theoretical approach to develop Intercultural Bioethics capable of including the views of allopathic medicine, as well as indigenous and ancestral medicine, in the biomedical discourse.
Keywords: Healthcare Ethics Committees; narrative bioethics; intercultural philosophy; bioethical decisions